INFLUENCE OF AEROBIC EXERCISE TRAINING ON SERUM MARKERS OF OXIDATIVE STRESS IN DIABETIC RATS - Pereira, Aron Da Silva; Spagnol, Alexandre Roveratti; Luciano, Eliete; Leme, José Alexandre Curiacos De Almeida (Universidade Estadual de Maringá, 2016)
ABSTRACT To verify the effects of exercise on blood biomarkers of oxidative stress in diabetic rats, 40 rats Wistar, were distributed into four groups: control, diabetes, trained control and trained diabetes. Training was constituted of swimming 1 hour/day, 5 days/week for 8 weeks with intensity equivalents to minimum lactate. Diabetes was induced with intravenous alloxan (32 mg/kg). It was evaluated the following blood parameters: catalase, superoxide dismutase (SOD), Malondialdehyde (MDA), glucose, cholesterol, triglycerides and C-reactive-protein. Diabetes induced hyperglycemia, reduction in body mass, catalase and SOD activities and increased TBARs concentrations. Physical training, on the other hand, reduced blood glucose and cholesterol, increased body mass and blood catalase. SOD activity was lower in diabetic rats than control rats and physical training was able to recovery this parameter. The other parameters showed no differences. In conclusion, physical exercise protocol contributes in controlling blood glucose, and ameliorates oxidative stress by increasing catalase levels and recovery SOD activity.

RESUMO Para verificar o efeito do exercício físico sobre biomarcadores de estresse oxidativo no sangue de ratos diabéticos foram utilizados 40 ratos Wistar distribuídos nos grupos controle, treinado, diabéticos e diabéticos treinado. O treinamento físico consistiu de natação 1 hora/dia, 5 dias/semana por 8 semanas. O diabetes foi induzido utilizando aloxana (32mg/kg). Foram analisados os parâmetros séricos: glicose, colesterol, triglicerídeos, proteína c reativa, catalase, superóxidodismutase (SOD) e malondialdeído (MDA). O diabetes aumentou as concentrações séricas de glicose e TBARs, porém diminuiu as atividades da SOD e catalase. O treinamento físico reduziu os níveis séricos de glicemia, colesterol e aumentou e catalase nos animais diabéticos. A atividade da SOD nos animais diabéticos foi menor que nos controles, sendo este parâmetro recuperado pelo treinamento físico. Não houve diferenças significativas nos demais parámetros estudados. Pode ser concluído que o treinamento físico foi eficaz em amenizar a hiperglicemia e o estresse oxidativo emanimais diabéticos.
INFLUÊNCIA DO TREINAMENTO FÍSICO AERÓBIO NOS MARCADORES SÉRICOS DE ESTRESSE OXIDATIVO EM RATOS DIABÉTICOS
Keywords: Exercise; Diabetes; Oxidative stress; Blood; Rats; Exercício; Diabetes; Estresse oxidativo; Sangue; Ratos